Chemical composition and amino acid profile of manyung fish (Arius thalassinus) from Subang, Indonesia - Dita Kristanti; Woro Setiaboma; Achmat Sarifudin; Dewi Desnilasari; Diki Nanang Surahman; Devry Pramesti Putri (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Manyung fish (Arius thalassinus) is one type of giant catfish in tropical areas, including Indonesia. Generally, the A. thalassinus was processed as a salted or smoked fish in Indonesia. There was no report for the proximate, specific mineral, and amino acid composition of A. thalassinus from the Subang region in West Java. This study aimed to analyze the chemical composition of A. thalassinus meat from Subang, West Java, which includes proximate minerals and amino acid composition. The sampling of A. thalassinus was conducted in triplicates by purposive sampling based on the length and weight of the fish. Furthermore, the fish were analyzed for moisture, ash, protein, fat, calcium, iron, zinc, and total amino acids (after acid hydrolysis). The proximate composition of the fish meat consisted of moisture (76.27±0.31% wb), ash (1.32±0.09% wb), protein (21.01±0.22% wb), and fat (0.34±0.03% wb). In this meat, minerals of calcium (12.11±0.14 mg/100g), iron (0.67±0.01 mg/100g), and zinc (0.67±0.01 mg/100 g) were not potential as micronutrient sources. The amino acid composition of A. thalassinus consisted of isoleucine (57.24±0.44 mg/g), leucine (194.03±1.97 mg/g), threonine (118.01±0.75 mg/g), valine (0.55±0.12 mg/g), serine (68.75±0.03 mg/g), alanine (52.50±0.20 mg/g), aspartate (142.43±0.16 mg/g), cysteine (2.72±0.12 mg/g), glutamate (192.20±0.28 mg/g), glycine (7.45±0.39 mg/g), and proline (0.13±0.04 mg/g). The main chemical composition of manyung fish meat was a protein with leucine, threonine, aspartate, and glutamate as the main amino acids. The protein content, especially leucine and aspartate, and the calcium content in A. thalassinus meat, can potentially support children's growth.